Pollution and Risk Assessment of Heavy Metals in the Sediments and Soils around Tiegelongnan Copper Deposit, Northern Tibet, China - Yuhu Luo; Qinxian Jia (Journal of Chemistry)
The surface sediments of the Rongna River and the surface soils around the Tiegelongnan copper deposit were collected, and the heavy metals Cu, Zn, Pb, Cr, Cd, As, Hg, and Ni were measured for their concentrations and health risk assessment. When the Rongna River passed through the Cu deposit area, the concentrations of Cu, Zn, As, Cd, Ni, and Hg in the surface sediments increased significantly, and the concentrations of Cu, Zn, and As exceeded the corresponding Grade II environmental quality standard. The heavy metals in the soil of the mining area were greater than the background value of the soil in Tibet. The geoaccumulation index indicated that the sediments of the river entering the mining area were very highly polluted by Cu and moderately polluted by Cd and Zn, and the soils in the mining area were moderately polluted by Cu. The potential ecological risk (PER) indices revealed that the sediments of the river entering the mining area had significantly high ecological risks, while the PER of the sediments away from the river section of the mining area was low, and the PER of the soils around the Cu deposit was moderate. The results of the health risk assessment indicated that the noncarcinogenic risks of heavy metals in sediments and soil of the mining area were within the acceptable range for adults and children. However, the carcinogenic risk of As and Cd in the sediment and As in the soil exceeds the relevant national standards, which may pose a certain risk to human health.